KEPUASAN PENGUNJUNG TERHADAP PRASARANA DAN SARANA DESTINASI WISATA RANCA UPAS DI KABUPATEN BANDUNG, PROVINSI JAWA BARAT - Lingara, Lasmia Saleh; Handawati, Rayuna; Mataburu, Ilham B (Social Landscape Journal, 2023)
Study aims to determine visitor satisfaction with tourist destination infrastructure and facilities at Ranca Upas Bandung Regency using a quantitative descriptive analysis research method. The sampling technique in this study was by accidental sampling technique with 56 respondents and processed using a Likert scale. Based on the results of the study, West Java Province was the origin of the most visitors in this study, and assessing the infrastructure facilities provided by the Ranca Upas tourist destination was very satisfied. Meanwhile, the least number of visitors came from East Java Province who assessed that the infrastructure and facilities at Ranca Upas were very dissatisfied. The most popular tourist attractions at Ranca Upas tourist destinations are deer breeding, this is because respondents can interact directly with deer along with affordable deer food prices, while what is less desirable is the Outbound area which is quite far from other attractions and there are no directions. make visitors do not know the location of the outbound area. From the data above, the majority of visitors are quite satisfied with all infrastructure and facilities.